SYNTHESIS, CHARACTERIZATION AND ANTIMICROBIAL ACTIVITY OF SOME TRANSITION METALS COMPLEXES DERIVED FROM BIS-PYRAZOLINE BASED LIGAND: Synthesis, Characterization and Antimicrobial Activity of Some Transition Metals Complexes - Aljibouri, Mahmoud Najim; Fahad, Abdul Rahman Maher (Malaysian Journal of Science, 2019)
A series of binuclear transition metal complexes with a general composition of (M2L(H2O)2Cl3) where (M=Mn(II), Co(II), Ni(II) and Cu(II), L=.5,5’-(5-(tert-butyl)-2-hydroxy-1,3-phenylene)bis(3-methyl-4,5-dihydro-1H-pyrazole-1-carbothioamide) are reported herein. The new pyrazoline ligand was synthesized via the ring closure of 4,4’-(5-(tert-butyl)-2-hydroxy-1,3-phenylene)bis(but-3-en-2-one) in an alkaline solution of thiosemicarbazide after adjusting the stoichiometric ratios of the reactants. The new bis-2-pyrazoline was fully characterized by EIMS, NMR, FT-IR and elemental analyses upon completion of the TLC technique. The metal complexes of the new ligand were isolated in their solid state after adjusting the mole ratios (M:HL) 2:1 through the reaction of the metal chlorides with the ethanolic solution of the ligand (HL). The metal complexes were fully characterized by elemental analysis, molar conductance, molecular weight determination, FT-IR, UV-Visible and magnetic measurements. Molecular weight determination of these complexes indicate a binuclear nature. The octahedral geometry was confirmed on the basics of electronic spectra and magnetic measurement together with spectral and flame atomic absorption data. The zinc (II) complex was tetrahedral geometry with the formula Zn2LCl3. The complexes are non-electrolytic in nature negligible molar conductance. The anti-microbial activities of these derivatives have been studied by screening them against bacteria such as Staphylococcus aureus and Eschericheia Coli and fungi such as Aspergillus nidulece and Condida albicance by the serial dilution method.